2023
DOI: 10.3390/jcm12082783
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implant and Customized Healing Abutment for a Periodontally Compromised Socket: 1-Year Follow-Up Retrospective Evaluation

Abstract: Immediate dental implant placement with or without immediate loading is reported in daily dentistry and implantology, but these procedures are not common in the case of periradicular and periapical lesions around the tooth needed to be replaced. In the following retrospective evaluation, 10 cases with a 1-year follow-up were selected to propose the technique of an immediate provisional non-loading prosthesis being delivered on the same day of the post-extraction implant placement in multiradicular teeth affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The use of a CAD/CAM technique to fabricate a perfectly adapted PMMA healing abutment is a growing subject but is almost limited to description of techniques and case reports in terms of scientific evidence (Ruales-Carrera et al, 2019;Thoma et al, 2019). This approach has been described as a beneficial solution that permits to reproduce precisely the contours of the root cervical area, maintaining and personalizing peri-implant tissues architecture during the healing phase (Menchini-Fabris et al, 2020). Also, they allow to reduce postoperative discomfort and morbidity by avoiding a second stage surgery for dental implant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a CAD/CAM technique to fabricate a perfectly adapted PMMA healing abutment is a growing subject but is almost limited to description of techniques and case reports in terms of scientific evidence (Ruales-Carrera et al, 2019;Thoma et al, 2019). This approach has been described as a beneficial solution that permits to reproduce precisely the contours of the root cervical area, maintaining and personalizing peri-implant tissues architecture during the healing phase (Menchini-Fabris et al, 2020). Also, they allow to reduce postoperative discomfort and morbidity by avoiding a second stage surgery for dental implant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the rehabilitation of the mandibular incisors and/or maxillary lateral incisors (MI/MxLI) is a challenge for clinicians. Immediate dental implants could be a good treatment choice, but this kind of surgery is not always possible [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a history of periodontitis was associated with significant marginal bone loss, higher implant failure rates, and more complications, including peri-implantitis, in the immediate implantation [ 20 , 21 ]. However, some studies have indicated that successful osseointegration could occur when implants were placed at previously infected sites [ 22 , 23 ]. Furthermore, clinical studies were reporting no significant difference in the clinical success of immediate implantation between sites with or without pre-existing periodontitis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%